Genome-wide association study reveals the genetic basis of brace root angle and diameter in maize - Sun, Daqiu; Chen, Sibo; Cui, Zhenhai; Lin, Jingwei; Liu, Meiling; Jin, Yueting; Zhang, Ao; Gao, Yuan; Cao, Huiying; Ruan, Yanye (Frontiers in Genetics, 2022)
Brace roots are the main organ to support the above-ground part of maize plant. It involves in plant growth and development by water absorption and lodging resistance. The bracing root angle (BRA) and diameter (BRD) are important components of brace root traits. Illuminating the genetic basis of BRA and BRD will contribute the improvement for mechanized harvest and increasing production. A GWAS of BRA and BRD was conducted using an associated panel composed of 508 inbred lines. The broad-sense heritability for BRA and BRD reached 71% and 52%. The phenotypic variation of BRA and BRD in the non-stiff stalk subgroup (NSS) and the stiff stalk subgroup (SS) subgroups are significantly higher than that in the tropical/subtropical subgroup (TST) subgroups. In addition, BRA and BRD are significantly positive with plant height (PH), ear length (EL), and kernel number per row (KNPR). GWAS revealed 27 candidate genes within the threshold of P < 1.84×10-6. Among them, three genes, GRMZM2G174736, GRMZM2G445169 and GRMZM2G479243 were involved in cell wall function, and GRMZM2G038073 encoded the NAC transcription factor family proteins. These results provides theoretical support for clarifying the genetic basis of brace roots traits.